Reflexões Críticas sobre o Ensino-Aprendizagem de Inglês como Fator de Inclusão ou Exclusão Social - Pereira, Paula Graciano (BELT - Brazilian English Language Teaching Journal, 2015)
This article discusses the mythological constructions of the English language and of its status as an international language, as well as the material implications of these constructions, mainly in the field of education, specifically in English teaching. This work followed three main theoretical guidelines: 1) the post-modern critical reflections, based on Makoni and Pennycook (2007) and Pennycook (2007), who understand languages as inventions of social, political and cultural movements; 2) the notions of discourse appropriation and social change through discourse, proposed by Fairclough (1999, 2001) and; the discussions about critical teaching, according to Jordão and Fogaça, 2012; Pessoa and Urzêda-Freitas, 2012; Urzêda-Freitas, 2012; Walters, 2012. It is defended that the English language, as a political-ideological instrument, can work, on the one hand, as a means of installing and maintaining material and cultural domination. However, on the other hand, it can serve as a toll to enhance awareness and social change.